2022
DOI: 10.3389/fnagi.2022.886023
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic function predicts cognitive decline in mild cognitive impairment: Evidence from power spectral analysis of heart rate variability in a longitudinal study

Abstract: Background: Despite the emerging clinical relevance of heart rate variability (HRV) as a potential biomarker of cognitive decline and as a candidate target for intervention, there is a dearth of research on the prospective relationship between HRV and cognitive change. In particular, no study has addressed this issue in subjects with a diagnosis of cognitive status including cognitive impairment.Objective: To investigate HRV as a predictor of cognitive decline in subjects with normal cognition (NC) or Mild Cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
46
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(52 citation statements)
references
References 92 publications
0
46
0
Order By: Relevance
“…The publication time frame spanned 14 years, from 2008 [ 66 ] to 2022 [ 72 , 73 , 74 , 75 ] with two thirds of studies clustered in the present decade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The publication time frame spanned 14 years, from 2008 [ 66 ] to 2022 [ 72 , 73 , 74 , 75 ] with two thirds of studies clustered in the present decade.…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 71 [ 74 ] to 5375 [ 66 ]. However, in two thirds of the studies the sample size was in the order of thousands.…”
Section: Resultsmentioning
confidence: 99%
“…for offering valuable information and discussion regarding the autonomic regulation and cognitive status. As mentioned in the “letter to the editor”, the authors observed that a higher sympathetic activation was related to cognitive decline whereas a greater parasympathetic HRV response predicted a lesser decline in executive functioning for MCI elderly [ 1 ]. Considering that the presence of cognitive impairment usually precedes the diagnosis of dementia, these results were compatible with our findings [ 2 ].…”
mentioning
confidence: 99%
“…The authors further addressed that the central autonomic network (CAN) may be a potential influencer of cognitive decline or dementia through the brain-heart axis [ 1 ]. Previous study has demonstrated that CAN modulates the pathogenesis of essential hypertension or orthostatic hypotension [ 3 ], which were crucial in the occurrence of dementia [ 4 ].…”
mentioning
confidence: 99%
“…In particular, there is increasing evidence that different components of the CAN are involved in different cognitive processes and in sympathetic versus parasympathetic autonomic control [ 2 , 4 ]. Accordingly, in a recent longitudinal study, we reported that, in older subjects with mild cognitive impairment, a greater HRV response to a sympathetic challenge predicted a greater decline in episodic memory whereas a greater HRV response to a parasympathetic challenge predicted a lesser decline in executive functioning [ 4 ].…”
mentioning
confidence: 99%